2022
DOI: 10.3389/fcvm.2022.916920
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Management of Ovarian Vein Thrombosis: A Case Series

Abstract: BackgroundOvarian vein thrombosis (OVT) is an uncommon condition, occurring in ~1 in every 600–2,000 pregnancies. It is associated with various conditions, including thrombophilia, malignancy, sepsis, intra-abdominal and pelvic inflammatory conditions, pregnancy, and the postpartum period, and specific surgical interventions, particularly gynecological surgeries. Thus, this study aims to identify the associated factors for OVT and elaborate on the standard treatment strategies for its management.MethodsRetrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
8
0
3
Order By: Relevance
“…In a multicenter study including 74 women with OVT of various etiologies, 89% had acute onset of symptoms, 7% had chronic symptoms, and 4% were asymptomatic [ 8 ]. Alsheef et al published a case series of retrospective data collection of patients diagnosed with OVT over an 11-year period [ 9 ]. The study concluded that the most common presentation was abdominal pain, followed by fever and vomiting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a multicenter study including 74 women with OVT of various etiologies, 89% had acute onset of symptoms, 7% had chronic symptoms, and 4% were asymptomatic [ 8 ]. Alsheef et al published a case series of retrospective data collection of patients diagnosed with OVT over an 11-year period [ 9 ]. The study concluded that the most common presentation was abdominal pain, followed by fever and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly user-dependent and can be limited by body habitus, overlying structures, and bowel gas patterns [ 10 ]. A CT venogram or CT scan of the abdomen and pelvis with contrast is highly sensitive and specific for the diagnosis and is time and cost-effective [ 9 ]. A retrospective study reported that magnetic resonance angiography (MRA) performed better than CT, making it the gold standard for the diagnosis of OVT [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Direct oral anticoagulants are discouraged in lactating mothers. It is yet debatable what the optimal duration is for the treatment 7 14. Multiple studies have described that treatment of 3 to 6 months seemed sufficient 9 14 15.…”
Section: Treatmentmentioning
confidence: 99%
“…[1] Standard treatment for OVT typically involves the use of low molecular weight heparin or warfarin for 1 to 3 months. [2,8]…”
Section: Introductionmentioning
confidence: 99%
“…[1] Standard treatment for OVT typically involves the use of low molecular weight heparin or warfarin for 1 to 3 months. [2,8] Pregnancy, a physiological state characterized by profound changes in hemostasis, confers an increased susceptibility to venous thromboembolism due to the multifaceted effects of Virchow triad, encompassing hypercoagulability, venous stasis, and endothelial injury. [9] Endothelial injury, a critical component of this triad, can occur during obstetric procedures such as vaginal and cesarean deliveries, and from uterine infections, further exacerbating the prothrombotic milieu associated with pregnancy.…”
Section: Introductionmentioning
confidence: 99%